Atomic‐Scale Investigations of H3BO3 and LiOH on Zr(0 0 0 1) Surface: A DFT Study. Issue 4 (8th February 2023) - Ren, Lu; Suo, Xinkun; LI, Guofu; Guo, Qi; Ruan, Dianbo; Zhang, Dongyang; Xu, Jian
Abstract: The boric acid (H3 BO3 ) and lithium hydroxide (LiOH) are routinely added to primary water as soluble neutron absorbers and pH regulating agents in the pressured water reactor nuclear power plant, respectively. Previous studies mostly focus on the service behavior of nuclear materials using experimental methods, whereas the microscopic mechanism of H3 BO3 and LiOH on Zr‐based fuel cladding remains largely unclear. With the first principle approach of density functional theory (DFT), the geometric structure, Mulliken population, partial densities of states, and electron density difference are adopted to study the adsorption characteristics and binding strength of H3 BO3 and LiOH on Zr matrix. The results show that when H3 BO3 and LiOH react on the Zr matrix, there is formation of hybrid peaks and new bonds between surface molecules and the matrix. Meanwhile, the vertical molecule has a substantial impact on electron movement between adsorbs and the matrix. The interaction energy between two molecules and the Zr surface in turn is LiOH > H3 BO3, demonstrating that LiOH has the most influence on the fuel cladding in the primary circuit. Abstract : Density functional theory is used to study the microscopic mechanism of H3 BO3 and LiOH on the Zr(0 0 0 1) surface. Investigation shows that the vertical molecules have a substantial impact on electron movement between adsorbs and matrix, which serves as an atom‐scale understanding of Zr alloy in the primary circuit of nuclear reactor.